Medium-term effect of sublingual l-glutathione supplementation on flow-mediated dilation in subjects with cardiovascular risk factors - Campolo, Jonica; Bernardi, Stefano; Cozzi, Lorena; Rocchiccioli, Silvia; Dellanoce, Cinzia; Cecchettini, Antonella; Tonini, Annamaria; Parolini, Marina; De Chiara, Benedetta; Micheloni, Gianpaolo; Pelosi, Gualtiero; Passino, Claudio; et al. (Nutrition (Burbank, Los Angeles County, Calif.), 2017)
Supplementation of glutathione (GSH) may be a positive strategy to improve the endogenous antioxidant defense required to counteract many acute and chronic diseases. However, the efficacy of GSH treatment seems to be closely related to type of administration, degree of absorption, and increase of its concentrations. The aim of this study was to test a new sublingual formulation of L-GSH, which enters directly the systemic circulation, to assess its efficacy on circulating biochemical markers of hepatic metabolism, lipid profile, and oxidative stress and on peripheral vascular function compared with placebo in patients with cardiovascular risk factors (CVRF). We enrolled 16 healthy men with CVRF in a double-blinded, randomized placebo-controlled crossover study. At each visit, blood samples were collected for biochemistry analyses and peripheral endothelial function (reactive hyperemia index [RHI]) and stiffness were measured by Endo-PAT2000. In the overall population, a decrease in total and low-density lipoprotein cholesterol was highlighted after L-GSH supplementation compared with placebo (P = 0.023 and P = 0.04, respectively). On the contrary, no difference was observed in RHI and oxidative stress markers between L-GSH and placebo in the study population. However, seven participants with baseline abnormal RHI (≤1.67) compared with those with normal RHI showed a significant reduction of arterial stiffness after L-GSH administration, (P = 0.007 and P = 0.037, respectively). Supplementation of L-GSH compared with placebo influences the lipid profile of patients with CVRF. Sublingual L-GSH may represent a valid prevention of vascular damage in patients with CVRF and endothelial dysfunction. •The presented study tested a sublingual formulation of l-glutathione (L-GSH) in men with cardiovascular risk factors.•We evaluated vascular function and biochemical markers.•L-GSH improved vascular elasticity in men with abnormal vasodilation.•L-GSH decreased total and low-density lipoprotein cholesterol in study participants.